The secrets of Abu Ghraib revealed : American soldiers on trial - Graveline, Christopher (Potomac Books, 2010)
"Christopher Graveline and Michael Clemens have produced a masterpiece of research and balance on a subject sure to evoke controversy and profound emotion. The nightmare of Abu Ghraib became the nadir of America's efforts in Iraq, yet the truth of what went on at the prison has remained--until now-- clouded by poor media coverage, politics, and the visceral reaction the infamous photos produced ail over the world. Graveline and Clemens are the firsr to provide us a complete picture of what happened at Abu Ghraib. Told will a compelling and sometimes shocking narrative, The Secrets of Abu Ghraib Repealed tanks as the seminal work on the Iraq Wan It is not to be missed."--John R. Bruning, author of The Devil's Sandbox: With the 2nd Battalion, 162nd Infantry at War in Iraq and coauthor of How to Break a Terrorist